1964
DOI: 10.1172/jci104985
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Volume Measurements in Man by Thermodilution*

Abstract: A safe, rapid method for estimating left ventricular volume in man during the course of hemodynamic studies should prove helpful in the assessment of cardiac disease and useful in physiological research. It is the purpose of this report to present left ventricular volume measurements in man that were obtained by an indicator dilution method which employs cold as the indicator. This circulatory indicator has been studied by several workers (1-4) and has been used for left ventricular volume determinations in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1964
1964
1975
1975

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…However, 6 of our patients studied by thermodilution had enddiastolic volumes within the normal range. These results are in close agreement with the findings of other workers who also report abnormally large enddiastolic volumes in some patients when measured by indicator dilution Bristow et al, 1964;Folse and Braunwald, 1962) and by angiocardiography (Jones et al, 1964). Linden and Mitchell (1960) have shown that in dogs the end-diastolic length of a ventricular muscle segment is related to end-diastolic pressure, and Braunwald et al (1960) have demonstrated that this also applies in man.…”
Section: Resultssupporting
confidence: 91%
“…However, 6 of our patients studied by thermodilution had enddiastolic volumes within the normal range. These results are in close agreement with the findings of other workers who also report abnormally large enddiastolic volumes in some patients when measured by indicator dilution Bristow et al, 1964;Folse and Braunwald, 1962) and by angiocardiography (Jones et al, 1964). Linden and Mitchell (1960) have shown that in dogs the end-diastolic length of a ventricular muscle segment is related to end-diastolic pressure, and Braunwald et al (1960) have demonstrated that this also applies in man.…”
Section: Resultssupporting
confidence: 91%
“…It is still debatable, however, whether an increase in left ventricular end-diastolic pressure is an accurate sign of left heart failure (Braunwald and Ross, 1963), since no correlation has been found between the end-diastolic pressure and the blood volume in the left ventricle in patients with mitral stenosis. The diastolic left ventricular volume in patients with mitral stenosis did not differ from that in the controls (Folse and Braunwald, 1962;Bristow et al, 1964;Gorlin et al, 1964). Dye dilution techniques, commonly used for estimating end-diastolic blood volume, give excessively high results (Bartle and Sanmarco, 1966;Carleton, Bowyer, and Graettinger, 1966).…”
Section: Resultsmentioning
confidence: 91%
“…It is also possible in such studies to construct indices of ventricular wall force and of velocity of ventricular wall shortening during systole utilizing measurements of left ventricular volume and pressure (18)(19)(20)(21). The present investigation was undertaken to determine whether or not it is feasible, utilizing thermodilution to measure left ventricular end-diastolic (LVEDV) and end-systolic (LVESV) volumes (22)(23)(24)(25), to apply the concepts of force-velocity and length-velocity relations of isolated cardiac muscle to the assessment of left ventricular adaptation in conscious normal human subjects. In this study, mean left ventricular wall force (MFE) and mean rate of circumferential shortening (MRCS) during ejection were calculated, assuming that the ventricle behaves as a contracting, thin-walled sphere.…”
Section: Introductionmentioning
confidence: 99%